Alternating-time temporal logic with resource bounds - Nguyen, Hoang Nga; Alechina, Natasha; Logan, Brian; Rakib, Abdur (Oxford University Press, 2015)
Many problems in AI and multi-agent systems research are most naturally formulated in terms of the abilities of a coalition of agents. There exist several excellent logical tools for reasoning about coalitional ability. However, coalitional ability can be affected by the availability of resources, and there is no straightforward way of reasoning about resource requirements in logics such as Coalition Logic (CL) and Alternating-time Temporal Logic (ATL). In this paper, we describe a logic for reasoning about coalitional ability under resource constraints. We extend ATL with costs of actions and hence of strategies. We give a complete and sound axiomatisation of the resulting logic, Resource-Bounded ATL (RB-ATL), and a model-checking algorithm for it.